2012
DOI: 10.1007/s12402-012-0097-z
|View full text |Cite
|
Sign up to set email alerts
|

Is emotional dysregulation part of the psychopathology of ADHD in adults?

Abstract: Attention-deficit hyperactivity disorder is a common condition in adulthood. The disorder is characterized by symptoms of inattention, hyperactivity, and impulsivity. Alongside these symptoms, it is discussed whether symptoms of emotional dysregulation could add additional and better description of the psychopathology of ADHD. Neither the current ICD-10 and DSM-IV nor the upcoming DSM-5 includes symptoms of emotional dysregulation as a core aspect of ADHD. Several authors (e.g., Wender 1995) describe adult ADH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(62 citation statements)
references
References 38 publications
4
57
0
1
Order By: Relevance
“…Current research leaves no doubt about the fact that emotional symptoms are frequent in ADHD and that these symptoms increase the risk of functional impairment as well as the severity of impairment. The findings of this study strengthen previous calls for including emotional symptoms in the theoretical conceptualization of diagnostic criteria for ADHD (Barkley 2010;Barkley and Fischer 2010;Barkley and Murphy 2010;Corbisiero et al 2012;Mitchell et al 2012). Because of their high impact on impairment, it is imperative to address emotional symptoms in diagnosis and therapy of ADHD.…”
Section: Limitations and Future Directionssupporting
confidence: 86%
See 1 more Smart Citation
“…Current research leaves no doubt about the fact that emotional symptoms are frequent in ADHD and that these symptoms increase the risk of functional impairment as well as the severity of impairment. The findings of this study strengthen previous calls for including emotional symptoms in the theoretical conceptualization of diagnostic criteria for ADHD (Barkley 2010;Barkley and Fischer 2010;Barkley and Murphy 2010;Corbisiero et al 2012;Mitchell et al 2012). Because of their high impact on impairment, it is imperative to address emotional symptoms in diagnosis and therapy of ADHD.…”
Section: Limitations and Future Directionssupporting
confidence: 86%
“…Because ADHD core symptoms cannot fully explain the number and severity of functional impairments (Anastopoulos et al 2011;Barkley 2010; Barkley and Fischer 2010;Barkley and Murphy 2010;Skirrow and Asherson 2013;Szuromi et al 2013), secondary domains, such as emotional symptoms, have become the focus of research over the past few years (overview: Corbisiero et al 2012;Retz et al 2012;Shaw et al 2014). Current studies reveal that the majority of people with ADHD report emotional symptoms (Barkley and Fischer 2010;Reimherr et al 2005) for which researchers use different definitions and labels such as emotional dysregulation (Wender 1995), emotional impulsiveness (Barkley 2006(Barkley , 2010, or emotional lability (Conners et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Surman et al (2013) also reported higher emotional symptoms leading to increased impairment in adults with ADHD. Corbisiero et al (2013) and Barkley (2010) argued that emotional symptoms are a fundamental part of the disorder, and Merwood et al (2014) presented genetic data pointing to a close association between hyperactivity/restlessness, impulsivity, inattention, and emotional dysregulation. Several studies have found that during treatment, emotional symptoms improve in parallel with the conventional symptoms of inattention, hyperactivity/ restlessness, and impulsivity Reimherr et al 2007;Rösler et al 2010;Wender et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Because of this developmental change in symptom expression, many adults will not fully exhibit the criteria for the diagnosis, while remaining significantly impaired (28). In addition to the core symptoms, ADHD in adults is strongly associated with emotional dysregulation (increased irritability, low tolerance for frustration and stress, emotional lability) (29). People with ADHD are a vulnerable group, in many cases with limited autonomy.…”
Section: Perspectivesmentioning
confidence: 99%